Make it count: maximising the stocking density of juvenile fluted giant clams (Tridacna squamosa Lamarck) during simulated live transportation - Gould, Andrew J. (2019)
Juvenile giant clams are usually transported at stocking densities of 1-2 bag¯¹ for up to 48 hr. In this study the effect of stocking juvenile fluted giant clams (Tridacna squamosa) at densities ranging from 2-19 bag¯¹ were assessed. Juveniles ranging from 50-70 mm in shell length (SL) and 11.3- 39.9g in wet weight (WW) were packed in plastic bags filled with 1L of 5µm-filtered seawater (FSW). The bags were then packed in styrofoam boxes and kept at 22.0-25.0 °C for 48hr. There was a relationship between stocking density and ammonia concentration of FSW, and inverse relationships between stocking density and pH, and stocking density and dissolved oxygen (DO). Following a 21 day resting period, no mortalities were recorded at stocking densities up to 13 juveniles. bag¯¹ . Both the WW and SL of juveniles in all treatments were significantly higher after the resting period than prior to the transportation trial. However, there was no relationship between stocking density and growth rate in either WW or SL. The results of this study suggest that juvenile T. squamosa can be transported without mortalities and effects on growth at a density of up to 13 juveniles. bag¯¹.